An autosomal dominant disorder with episodic ataxia, vertigo, and tinnitus. - Steckley, J; Ebers, G; Cader, M; McLachlan, R (2001)
The authors report an autosomal dominant episodic ataxia that is clinically distinct from the other episodic ataxias. Vestibular ataxia, vertigo, tinnitus, and interictal myokymia are prominent; attacks are diminished by acetazolamide. Linkage analyses of markers flanking the EA1 and EA2 loci demonstrate genetic exclusion from the other autosomal dominant episodic ataxias. The authors suggest EA3 for periodic vestibulocerebellar ataxia and EA4 for the disorder described here.